Idolatry and the construction of the Spanish empire - Soormally, Mina Garcia, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
An ethnohistory on the spiritual as well as governmental conquest of the indigenous people in colonial Mexico that examines the role the shifting concept of idolatry played in the conquest of the Americas, as well as its relation to the subsequent construction of imperial power and hegemony.--Provided by publisher.
The limits of idolatry -- Idolatry in New Spain and the peninsular laboratory -- Idolatry in New Spain: Zumárraga bishopric (1528-1548) -- From idolatrous to Marian: New Spain between Zumárraga and Montúfar.
Keywords: Catholic Church -- Mexico -- History; Idolatry -- Mexico -- History; Indians of Mexico -- Religion; Mexico -- Religion; Mexico -- Religious life and customs; Mexico -- History -- Spanish colony, 1540-1810